Integrated nutrient management and mulching for higher productivity of spur type apple (Malus domestica) cultivars - DAS, BISWAJIT; HAREKRISHNA; RANJAN, J K; PRAGYA; AHMED, N; ATTRI, B L (The Indian Journal of Agricultural Sciences, 2016)
Integrated nutrient combination comprising NPK sources from organic manures (FYM and vermicompost) and inorganic sources along with mulching (leaf mould and black polyethylene) were applied on apple (Malus domestica Borkh) cv. Starkrimson planted on high density system. The objective was to supplement NPK requirement by applying sufficient quantity of organic manures, thereby, minimizing the inorganic fertilizer requirement. Better result was obtained in treatment comprising leaf mould mulch and integrated nutrients: 50 kg/tree FYM + 10 kg/tree vermicompost + 50 g/tree N + 75 g/tree P2O5 + 250 g/tree K2O in 5th year; 60 kg/tree FYM + 13 kg/tree vermicompost + 30 g/tree N + 80 g/tree P2O5 + 225 g/tree K2O in 6th year; 70 kg/tree FYM + 16 kg/tree vermicompost + 10 g/tree N + 85 g/tree P2O5 + 250 g/tree K2O in 7th year and 70 kg/tree FYM + 19 kg/tree vermicompost + 165 g/tree N + 178 g/tree P2O5 + 548 g/tree K2O in both 8th and 9th year. In the 8th and 9th year, this treatment resulted comparatively higher fruit yield (31.8 and 30.6 kg/tree, respectively) and productivity (50.8 and 53.3 MT/ha, respectively) with fruit weight 200.4 and 202.4 g and diameter 8.4 and 8.2 cm, respectively. Whereas, in recommended dose, in 8th and 9th year, 27.6 and 25.6 kg/tree yield and 44.2 and 40.9 MT/ha productivity were recorded, respectively. Reduction of FYM quantity by 50% and increasing the vermicompost dose also supplemented considerable amount of NPK requirement from inorganic sources and resulted better plant growth and yield.